Strategi Program Acara Dakwah untuk Meningkatkan Eksistensi di Media Televisi - Maharani Amelia Putri; Muhammad Naufal Rahmatullah; Najah Fathin Nur Afsharina; Meity Suryandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In today's information and technology era, television media has a very important role in shaping opinions and influencing people's views. The existence of da'wah programs on television media is not only about increasing the number of impressions, but also how these programs can really permeate and have a positive impact on society. Therefore, the strategy of da'wah programs in television media requires special attention and in-depth study. The method in this article uses a literature study, which is a method with data collection by understanding and studying theories from various literature related to the research. From the results of the research, an attractive and quality program strategy is very important to increase the existence of da'wah programs on television media. In addition, cooperation with related parties and promotion through social media can also help increase the number of viewers. In the increasingly fierce competition of television media, da'wah programs must continue to innovate and adapt to technological developments and viewers' needs in order to remain effective in delivering da'wah messages. The effectiveness of da'wah programs on television media can be influenced by various factors. Therefore, several strategies can be used in da'wah programs on television media with a focus on how to improve the existence and effectiveness of da'wah messages.